Vers une réconciliation des théories et de la pratique de l’évaluation, perspectives d’avenir - Brousselle, Astrid (2006)
Evaluation practitioners encounter various questions while conducting evaluation projects. First, how can the evaluator define the intervention which is to be evaluated? Second, how should the evaluator consider the change? Third, how can use of the evaluation be encouraged? All three preoccupations have found answers in the theoretical developments of program evaluation, whether through implementation evaluation, intervention analysis or participative approaches. However, prolific theoretical developments, while enriching the strategies available to us, may also lead paradoxically to confusion and to difficulties in the transposition of new knowledge into practice. First, we will illustrate the three main difficulties the evaluator is confronted with during practice. Then we will review the different answers offered by evaluation theory. Finally, we will analyze the potential contributions and difficulties which these developments bring to evaluation practice. In conclusion, we will discuss future avenues for facilitating the appropriation of evaluation theories into practice.